Pemanfaatan Media Sosial sebagai Sarana Branding Sekolah: Analisis Isi Konten pada Akun Instagram SMP Islam Cendekia Cianjur - Najwa Hafifah; Suhaila Rasya; Ferry Dermawan (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2026)
This study analyzes the use of Instagram as a branding medium for SMP Islam Cendekia Cianjur through the @officialcendekia account. Using qualitative content analysis on 296 posts from June 2025 to May 2026, five content categories were identified: Informative (18.2%), Educative (14.9%), Achievement (30.4%), Religious (25.0%), and Engagement (11.5%). Achievement and Religious content dominated, reflecting a deliberate strategy to build perceived quality and brand association. Thematic analysis revealed four core values: academic excellence, religiosity, leadership, and competitive spirit. The account is strategically utilized to construct institutional identity, building brand equity and positioning the school as a competitive Islamic institution.